2018
DOI: 10.1503/cmaj.171509
|View full text |Cite|
|
Sign up to set email alerts
|

Identification and management of frailty in the primary care setting

Abstract: F railty is a dynamic state of heightened vulnerability to stress ors. It is a multidimensional syndrome that places individuals at risk for adverse health outcomes, including falls, disability, admission to hospital and death. 1 The prevalence of frailty rises with advancing age, from 16% in people older than 65 years to rates as high as 52% in those older than 85 years. 2 It is associated with many comorbidities and is more common among women 3 and individuals with lower socioeconomic status. 4 Frailty is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
72
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(74 citation statements)
references
References 73 publications
1
72
0
1
Order By: Relevance
“…A self-administered tool able to evaluate frailty is currently a target for welfare and health-care systems, since the self-perception of frailty could yield a wider assessment and enable frailty to be diagnosed earlier. 29 So far, the self-assessment of frailty has been used only for screening purposes. Moreover, a systematic review found a total of 10 self-administered tools for assessing frailty in primary care and concluded that the Tilburg Frailty Indicator and the SHARE Frailty Index were the only suitable ones.…”
Section: Discussionmentioning
confidence: 99%
“…A self-administered tool able to evaluate frailty is currently a target for welfare and health-care systems, since the self-perception of frailty could yield a wider assessment and enable frailty to be diagnosed earlier. 29 So far, the self-assessment of frailty has been used only for screening purposes. Moreover, a systematic review found a total of 10 self-administered tools for assessing frailty in primary care and concluded that the Tilburg Frailty Indicator and the SHARE Frailty Index were the only suitable ones.…”
Section: Discussionmentioning
confidence: 99%
“…The mental domain can present mental frailty with cognitive, mood or motivational consequences. Cognitive frailty should be distinguished from physical frailty and dementia (5,8,9). Social frailty depends on the loss of social or general resources, self-care skills, and social behaviours and activities that an individual needs (5,10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Stratification of subjects employing these instruments requires a lengthy process, comprising several questionnaires and complex physical assessments, both requiring high levels of geriatric expertise [9]. Because of these requirements, use of both instruments is limited to specialized teams which means that neither can be transposed to primary care [2,5,15]. Another instrument, the Vulnerable Elders Survey-13 (VES-13), also can be employed to predict the risk of functional decline, institutionalization, or death in the elderly, [16,17].…”
Section: Introductionmentioning
confidence: 99%